ChemInform Abstract: Experimental Investigation of the Phase Diagram of the Fe‐Pd‐Nd Ternary System at 773 K. Issue 48 (10th November 2016) - Du, Y.s.; Li, C. R.; Cheng, G.; Sun, Y. Z.; Wu, X. F.; Yao, Q. R.
Abstract: The 773 K isothermal section of the title system is investigated by XRD, SEM, DSC, and EDS techniques.